Genetic selection for peptide inhibitors of angiogenin - Smith, Bryan D. (2008)
The improper regulation of angiogenesis is implicit in a variety of diseases, including cancer. Angiogenin is unique among angiogenic factors in its having ribonucleolytic activity. Inhibitors of this activity could serve as chemotherapeutics. The ribonucleolytic activity of angiogenin is toxic to the Origami™ strain of Escherichia coli. Herein, this cytotoxicity was used to identify inhibitors from a random nonapeptide library tethered to the C-terminus of human angiogenin. The selected sequences fell into three classes: (1) extremely hydrophobic, (2) putative ClpXP substrates, and (3) slightly anionic. Two peptides corresponding to sequences in the last class were synthesized chemically and found to inhibit the ribonucleolytic activity of human angiogenin in vitro with micromolar values of K(i). Both peptides also inhibit bovine pancreatic ribonuclease, a homologue of angiogenin, though one exhibits selectivity for angiogenin. The affinity and selectivity of these peptides are comparable to the best known inhibitors of angiogenin. Moreover, the strategy used to identify them is general and could be applied to other cytotoxins.